Spontaneous rupture of a splenic artery aneurysm causing acute abdomen in a 19-year-old male patient: a case report - Njoum, Yumna; Barqawi, Abdallah Deghles; Maree, Mohammed (Frontiers in Surgery, 2023)
Introduction A splenic artery aneurysm is considered an abnormal dilatation of the splenic artery layers greater than 1 cm in diameter. First described by Beaussier in 1770, it affects 1% of the population but carries a major risk for life-threatening complications of rupture in 3%–10% of cases regardless of its congenital or acquired etiology. The presentation is highly variable, from asymptomatic incidental discovery during routine imaging to aneurysmal rupture causing acute abdomen, massive gastrointestinal bleeding, and hemorrhagic shock. Case presentation Herein, we present a 19-year-old male patient who presented with epigastric pain and abdominal rigidity associated with a moderate amount of free peritoneal fluid that was found to be a ruptured SAA after immediate laparoscopy, which was successfully managed with splenectomy. Conclusion SAAs are a rare etiology of acute abdomen and hemorrhagic shock but have a very high risk of mortality even upon immediate intervention, requiring a very high level of vigilance and a low threshold for surgical intervention in unstable patients presenting with abdominal pain.